2020
DOI: 10.1111/jocs.15176
|View full text |Cite
|
Sign up to set email alerts
|

Unique technical challenges in patients undergoing TAVR for failed aortic homografts

Abstract: Objective: Surgical reoperation for aortic homograft structural valve degeneration (SVD) is a high-risk procedure. Transcatheter aortic valve replacement (TAVR) for homograft-SVD is an alternative to reoperation, but descriptions of implantation techniques are limited. This study compares outcome in patients undergoing into two groups by the type of previously implanted aortic valve prosthesis: TAVR for failed aortic homografts (TAVR-H) or for stented aortic bioprostheses (TAVR-BP). Methods: From 2015 to 2017,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Kislitsina et al. 3 compared the outcomes of 41 patients undergoing TAVI because of aortic valve degeneration, 33 with failed stented aortic bioprostheses and eight with failed homografts. The bioprosthesis group presented predominantly with prosthesis stenosis (94%, P = .002), whereas the homograft group showed mostly aortic regurgitation (88%, P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Kislitsina et al. 3 compared the outcomes of 41 patients undergoing TAVI because of aortic valve degeneration, 33 with failed stented aortic bioprostheses and eight with failed homografts. The bioprosthesis group presented predominantly with prosthesis stenosis (94%, P = .002), whereas the homograft group showed mostly aortic regurgitation (88%, P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Homograft failure typically results in aortic regurgitation and the implant technique for aortic VIV is not established, owing to the variability of the proximal suture line of the homograft. 20 On the other hand, reoperation for failed homograft is more challenging than for failed AVR owing to homograft calcification, which is often severe. Comparative studies have paralleled those for aortic VIV for stented bioprosthesis in terms of early mortality and perioperative complications, 21 but some centers including ours have shown that late valve migration may be a concern.…”
Section: Benefits Of Tavr Approachmentioning
confidence: 99%
“…Comparative studies have paralleled those for aortic VIV for stented bioprosthesis in terms of early mortality and perioperative complications, 21 but some centers including ours have shown that late valve migration may be a concern. 20 Thus, although aortic VIV for failed aortic homografts is feasible, long-term outcomes deserve attention.…”
Section: Benefits Of Tavr Approachmentioning
confidence: 99%
“…Transcatheter AVR (TAVR) may be a less risky approach in the absence of infection for both homografts or xenografts and bioprosthetic valve composite conduits, but long-term results will have to follow, particularly in the young patient. 20,21 The development of a modular biological prosthetic valvesynthetic graft conduit would provide a technical advancement for the BioBentall. A simplified technique should minimize risk not only at the time of the primary operation but also at the time of an inevitable reintervention due to structural valve deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Transcatheter AVR (TAVR) may be a less risky approach in the absence of infection for both homografts or xenografts and bioprosthetic valve composite conduits, but long-term results will have to follow, particularly in the young patient. 20,21…”
Section: Introductionmentioning
confidence: 99%